An empirical study on the utility of formal routines to transfer knowledge and experience. - Conradi, Reidar (Software engineering notes.)
Most quality and software process improvement frameworks emphasize written (i.e. formal) documentation to convey recommended work practices. However, there is considerable skepticism among developers to learn from and adhere to prescribed process models. The latter are often perceived as overly "structured" or implying too much "control". Further, what is relevant knowledge has often been decided by "others"---often the quality manager. The study was carried out in the context of a national software process improvement program in Norway for small- and medium-sized companies to assess the attitude to formalized knowledge and experience sources. The results show that developers are rather skeptical at using written routines, while quality and technical managers are taking this for granted. This is an explosive combination. The conclusion is that formal routines must be supplemented by collaborative, social processes to promote effective dissemination and organizational learning. Trying to force a (well-intended) quality system down the developers' throats is both futile and demoralizing. The wider implications for quality and improvement work is that we must strike a balance between the "disciplined" or "rational" and the "creative" way of working.